Pengasuhan Santri di Pesantren - Handayani, Yekti; Setyariza, Nur Ayu; Kusumawardani, Intan; Widawati, Sri Erna; Anshory, Muhammad Isa (TSAQOFAH, 2024)
In Islamic boarding schools, responsibility is given to the kiai as educators who will educate their children by adhering to religion. Kiai gives responsibility to his students to form good morals and personalities. This responsibility is applied in the education of children which is often called parenting. In this way, the parenting style of parents (kiai and nyai mother) plays a very important and determining role, as well as laying the foundation for education or for the child's development in accordance with the child's basics. This research aims to determine the parenting patterns that exist in Islamic boarding schools. The method used by researchers is library research or literature study. The results obtained from this research are that the role of the caregiver is to control and supervise the students and the relationship between the two is closer. It is commonplace that most Islamic boarding schools use an authoritarian parenting style. So whatever the teacher orders, the students must obey.